Fallen Angels : Covet - Book 1 - Ward, J. R., 1969- (New York : Signet, 2009)
"Redemption isnt a word Jim Heron knows much about--his specialty is revenge, and to him, sin is all relative. But everything changes when he becomes a fallen angel and is charged with saving the souls of seven people from the seven deadly sins. And failure is not an option. Vin diPietro has surrendered himself to his business--until fate intervenes in the form of a tough-talking, Harley- riding, self-professed savior, and a woman who makes him question his destiny. With an ancient evil ready to claim him, Vin has to work with a fallen angel not only to win his beloved over ... but to redeem his very soul."--Page 4 of cover.
"An explosive new series"--Page 4 of cover.
Keywords: Deadly sins -- Fiction; Angels -- Fiction; Redemption -- Fiction; Supernatural -- Fiction; Paranormal fiction; Romance fiction